The Role of Acute Intermittent Hypoxia in Neutrophil-Generated Superoxide, Sympathovagal Balance, and Vascular Function in Healthy Subjects - Almeida, Germana P. L.; Trombetta, Ivani C.; Cepeda, Felipe X.; Hatanaka, Elaine; Curi, Rui; Mostarda, Cristiano; Irigoyen, Maria C.; Barreto-Filho, José A. S.; Krieger, Eduardo M.; Consolim-Colombo, Fernanda M. (Frontiers in Physiology, 2017)
Introduction. Recurrent hypoxia (HPX), a hallmark of the obstructive sleep apnea (OSA), impairs autonomic balance and increases arterial blood pressure (BP). Oxidative stress is one of the mechanisms involved in these alterations. The cumulative effect of acute intermittent HPX and the chronicity may determine whether the response crosses the threshold from having protective value to pathology. However, the impact of acute intermittent HPX–reoxygenation on markers of oxidative stress in healthy individuals remains to be fully understood. Objective. To analyze the effects of the acute intermittent HPX on the generation of neutrophil-derived superoxide, sympathovagal balance and vascular function in healthy subjects. Methods. We applied six cycles of intermittent HPX (10% O2 and 90% N2) for 5 min followed by 2 min of room-air in 15 healthy volunteers (34±2y; 22.3±0.46kg/m2), without OSA (polysomnography), during wakefulness. During the experimental protocol, we recorded O2 saturation, end-tidal CO2, heart rate (HR), systolic and diastolic BP, cardiac output (CO) and peripheral resistance (PR). Cardiac sympathovagal balance was determined by HR variability analysis (low frequency and high frequency bands, LF/HF). Superoxide generation in polymorphonuclear neutrophil cells were established using relative luminescence units (PMNs RLU) at baseline (pre-HPX) and immediately after hypoxia induction (post-HPX6). Results. The studied subjects had normal levels of BP, plasma glucose, lipid profile and inflammatory marker (C-reactive protein). Acute intermittent HPX increased HR, systolic BP, CO and decreased PR. Additionally, acute intermittent HPX increased PMNs RLU, measured post-HPX6 (470±50 vs. 741±135, P<0.05). We found a similar increase in LF/HF post-HPX6 (0.91±0.11 vs. 2.85±0.40, P<0.05). PR was diminished from pre-HPX to post-HPX6 (1.0±0.03 vs. 0.85±0.06, P<0.05). Further analysis showed significant association between O2 saturation and PMNs RLU (R=−0.62, P=0.02), and with LF/HF (R=−0.79, P=0.02) post-HPX6. In addition, an association was found between PMNs RLU and PR post-HPX6 (R=0.58, P=0.04). Conclusion. Acute exposure to intermittent HPX not only increased superoxide generation in neutrophils, but also impaired cardiac sympathovagal balance in healthy subjects. These data reinforce the role of intermittent HPX in superoxide generation on neutrophils, which may lead to an impairment in peripheral vascular resistance.